Late effects in pediatric Hodgkin lymphoma survivors after uniform treatment with ABVD with or without radiotherapy. Issue 11 (25th August 2021) - Mittal, Abhenil; Bhethanabhotla, Sainath; Ganguly, Shuvadeep; Vishnubhatla, Sreenivas; Khadgawat, Rajesh; Patel, Chetan; Mohan, Anant; Biswas, Ahitagni; Bakhshi, Sameer
Abstract: Purpose: ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine) is not a standard regimen in children due to concerns regarding late effects. However, no studies have evaluated long‐term toxicities of ABVD in children. Methods: Total 154 pediatric Hodgkin lymphoma (HL) survivors uniformly treated with ABVD were clinically followed up as per institutional protocol. All participants were evaluated for cardiac, pulmonary, and thyroid function abnormalities by multigated acquisition scan (MUGA) scan, spirometry with diffusion capacity of lung for the uptake of carbon monoxide (DLCO), and thyroid profile test, respectively, at a single time point. Predictors of toxicity were also analyzed. Results: The median duration of follow‐up of the cohort was 10.3 years (6.04–16.8). No secondary malignant neoplasm (SMN) or symptomatic cardiac/pulmonary toxicities were detected. Nine patients (5.9%) had left ventricular ejection fraction (LVEF) <55%. Subclinical and overt hypothyroidism were observed in 78 (50.6%) and 16 (10.4%) survivors, respectively. Abnormal spirometry and reduced DLCO was observed in 43.2% and 42.0% survivors, respectively. Receiving neck radiation was significantly associated with thyroid dysfunction (odds ratio [OR] 16.04, p < .001); age ≥10 years predicted reduced DLCO (OR 4.12, p = .001). Sixty‐three and 33 patients had one and two late adverse effects, respectively; receiving neck radiation predicted development of multiple late effects (proportional OR 4.72, p < 0.001). Cumulative dose of chemotherapy did not predict toxicity. Conclusions: Overall, ABVD appears safe in children at a relatively short follow‐up. Long‐term safety data are required before it can be adopted for treating pediatric HL patients. Children receiving neck radiation require close follow‐up.